Unraveled - Hardt, Helen (Hardt, Helen. Steel brothers saga ;, 2018)
Ryan Steel and Ruby Lee are in love, but before they can move forward with a life together, theyre determined to bring resolution to the many unanswered questions they still face. To complicate matters, new threats arise with the arrival of two startling figures from their pasts. As they race against time to find answers, unexpected forces pull them apart. Ryan's brothers, Talon and Jonah, rally to help, wanting to end the struggle and finally bring the last perpetrators to justice. But another riddle surfaces, deepening the rift between Ruby and Ryan. Will they salvage their relationship and finally unravel the mysteries surrounding them?